Radioprotective effects of copper and manganese schiff base complexes against 6 MeV electron beam on breast cancers cells - Rahman, Wan Nordiana; Talik Sisin, Noor Nabilah; Ab Rashid, Raizulnasuha; Mohamed, Faizal; Ismail, Fuad; Sidek, Khairiyah; Algethami, Merfat; Assran, Awatef S. (Elsevier, 2025)
Purpose: Targeting breast cancer with radiotherapy demand a strategy by maximizing high dose radiation whilst crucially ensure the neighbouring healthy tissues can be preserved and protected from radiation exposure. In order to diminish this negative effect some radioprotector element seem essential. Current approach of using metal complexes as radioprotector in radiation therapy had shown a promising outcome in advanced targeted radiotherapy. Methods: Cu and Mn NPs complexation with two Schiff bases (L2, and L3) were evaluated for their cytotoxicity and free radical scavenging activities using DPPH test on MCF-7 and MDA MB-123 cancer cells. The radioprotective effect with 6 MeV clinical electron beam were evaluated using clonogenic assay. Results: The cytotoxicity test show that the Cu-L2, Cu-L3 and Mn-L2, Mn-L3 complexes are more toxic to MDA-MB-123 as compared to MCF-7 cancer cells. Mn-L2 and Cu-L2 are less toxic compare to Mn-L3 and Cu-L3 and were selected to be tested for irradiation study. The presence of the complexes during 6 MeV electron beam irradiation demonstrated that the Cu- L2 complex protected MCF-7 cells better than the Mn-L2 complex. The dose modifying ratio (DMR) measured show the value of Mn complexes is higher than that of Cu complexes. Finally, the DPPH free radical scavenging activities revealed that the Cu-L3, Mn-L3, and Mn-L2 complexes had poor antioxidative characteristics, whereas the Cu-L2 complex had intermediate antioxidative properties. Conclusion: The Cu-L2 compound is the most effective radioprotective agent compared to other compounds under investigation. The Mn-L3, Cu-L3 and Mn-L2 are found to be toxic with oxidative properties that might need further investigation for clinical application.